Normal adrenal gland thickness on computerized tomography in an Asian Indian adult population - John, Reetu; Putta, Tharani; Simon, Betty; Eapen, Anu; Jebasingh, Felix; Thomas, Nihal; Rajaratnam, Simon (Indian Journal of Radiology and Imaging, 2018)
Context: The size and morphology of the adrenal glands are affected by several physiological and pathological conditions. Radiologists need to be aware of the normal thickness of adrenal gland to accurately assess patients with suspected adrenal pathology. However, there is limited data on the normal size of the adrenal glands. Moreover, this has not been studied in our population. Aims: To study the normal thickness of adrenal gland on computerized tomography (CT) in Indian adult population. Settings and Design: Retrospective study in a tertiary care hospital in Southern India. Subjects and Methods: Our study included 586 adults who underwent a CT abdominal angiogram over 15 months, and excluding patients with clinical or imaging evidence of adrenal disease. The measurements made included: the maximum thickness of the body, medial and lateral limbs, measured perpendicular to the long axis. Results: The median age was 51 (range: 18–85) years. The mean maximum thickness of the adrenal body, medial, and lateral limbs were 7.2 ± 1.8, 4.1 ± 1.1, and 4.3 ± 1.1 mm on the right side and 8.8 ± 1.9, 4.7 ± 1.1, and 4.9 ± 1.3 mm on the left. The cumulative thickness of the body and the limbs were 15.6 ± 3.7 mm and 18.4 ± 3.8 mm on the right and left sides, respectively. There was a statistically significant difference in all the measurements between the right and left adrenal glands (all P values = 0.000) and between men and women, being larger in men (P value <0.05). Among our patients 27% had at least one adrenal gland body measuring ≥10 mm in thickness. Conclusions: Our study has defined the normal range of adrenal gland thickness in an Asian Indian adult population, which may be used as a baseline reference for future research and as a reference for radiological reporting.
Keywords: Adrenal atrophy; adrenal gland size; adrenal gland thickness; bulky adrenal; multidetector computed tomography